2010
DOI: 10.5551/jat.2741
|View full text |Cite
|
Sign up to set email alerts
|

Is Pentraxin 3 Involved in Obesity-Induced Decrease in Arterial Distensibility?

Abstract: Aim: Obesity is a strong risk factor for cardiovascular morbidity and mortality. In addition, decreased central arterial distensibility is recognized as an independent risk factor for cardiovascular disease (CVD). Obese subjects exhibit low arterial distensibillity; however, the mechanism responsible for the decrease in arterial distensibility in obese subjects has not yet been elucidated. Pentraxin 3 (PTX3), a recently identified member of the pentraxin family of proteins, is produced in areas of atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
2
21
2
Order By: Relevance
“…These results agree with the previous reports of inverse correlation between plasma PTX3 and fat mass (7), BMI (34,44), body weight, and waist circumference (34). They are in contrast to other studies (30,45) that report a positive link between PTX3, obesity, and some cardiovascular risk factors; i.e., higher circulating PTX3 was found in patients with metabolic syndrome in association with subclinical atherosclerosis (45), in obese men coexisting with decreased arterial distensibility (30), and in acute myocardial infarction patients in correlation with abdominal visceral obesity (40). There is no clear explanation for these discrepancies, and all of these results come from observational studies.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results agree with the previous reports of inverse correlation between plasma PTX3 and fat mass (7), BMI (34,44), body weight, and waist circumference (34). They are in contrast to other studies (30,45) that report a positive link between PTX3, obesity, and some cardiovascular risk factors; i.e., higher circulating PTX3 was found in patients with metabolic syndrome in association with subclinical atherosclerosis (45), in obese men coexisting with decreased arterial distensibility (30), and in acute myocardial infarction patients in correlation with abdominal visceral obesity (40). There is no clear explanation for these discrepancies, and all of these results come from observational studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Likewise, negative correlations between concentrations of plasma PTX3 protein and triglycerides and BMI and lower PTX3 values in individuals with metabolic syndrome were described in a large population of subjects (34,44). However, some recent studies (30,45) disagree with these associations, reporting a positive link between PTX3, obesity, and some cardiovascular risk factors that associates the inflammatory function of this pentraxin with a worse cardiovascular profile. There is little information about PTX3 gene expression in AT, although PTX3 mRNA levels are higher in the white AT of genetically obese (ob/ob) and obese diabetic (db/db) mice than in controls (1).…”
mentioning
confidence: 83%
“…Likewise, PTX3 has been suggested as a useful inflammatory biomarker for predicting cognitive impairment in elderly hypertensive patients (Yano et al 2010). Conversely, the assessment of PTX3 as a marker of metabolic syndrome characterized by increased cardiovascular risk has produced controversial data and further studies with larger number of patients are required before definitive conclusions can be made (Miyaki et al 2010;Ogawa et al 2010;Zanetti et al 2009). Increased levels of PTX3 have been observed in a restricted set of autoimmune disorders (e.g.…”
Section: Ptx3 As a Marker In Human Pathologymentioning
confidence: 95%
“…Changes in circulating PTX3 in human obesity remain however controversial. Initial studies reported higher plasma PTX3 in obese than in normal weight individuals (23,24) , but more recent general population reports suggest a negative impact of adiposity on plasma PTX3 (25)(26)(27)(28)(29) . Consistent with the latter findings, one study reported that weight loss induced by lifestyle changes enhances circulating PTX3 (29) .…”
Section: Introductionmentioning
confidence: 98%